Analogy mapping for different learning style of learners in programming - Sukamto, Rosa Ariani; Megasari, Rani (ICSITech : proceedings : 2017 3rd International Conference on Science in Information Technology : "Theory and application of IT for education, industry, and society in big data era" : October 25-26, 2017, Bandung, Indonesia, 2017)
Programming logic is often hard to understand for novice, but in the other side, programming is one of the most important subjects in computer science program. Analogy Mapping is a media which converts source code to analogies images using state machine in order to help students understanding programming logic easily. Therefore this paper reports our work about the effectivity of Analogy Mapping in learning process for basic programming subject students with different learning style.